2022
DOI: 10.1093/nar/gkac673
|View full text |Cite
|
Sign up to set email alerts
|

FOXL2 and FOXA1 cooperatively assemble on the TP53 promoter in alternative dimer configurations

Abstract: Although both the p53 and forkhead box (FOX) family proteins are key transcription factors associated with cancer progression, their direct relationship is unknown. Here, we found that FOX family proteins bind to the non-canonical homotypic cluster of the p53 promoter region (TP53). Analysis of crystal structures of FOX proteins (FOXL2 and FOXA1) bound to the p53 homotypic cluster indicated that they interact with a 2:1 stoichiometry accommodated by FOX-induced DNA allostery. In particular, FOX proteins exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Given the finding in our data and others of FOXL2 C134W positive tumors with diverse histology, we feel broader testing is justified. The involvement of FOXL2 gene mutations in cancer and the need for clinical testing is further supported by recent publications indicating a potential role of FOXL2 in cancer suppression, as FOXL2 is normally involved in the transcriptional activation of TP53 (17) and in stabilizing DNA double-strand break repair (18).…”
Section: Discussionmentioning
confidence: 87%
“…Given the finding in our data and others of FOXL2 C134W positive tumors with diverse histology, we feel broader testing is justified. The involvement of FOXL2 gene mutations in cancer and the need for clinical testing is further supported by recent publications indicating a potential role of FOXL2 in cancer suppression, as FOXL2 is normally involved in the transcriptional activation of TP53 (17) and in stabilizing DNA double-strand break repair (18).…”
Section: Discussionmentioning
confidence: 87%
“…However, the similar expression patterns of foxl2 and hsd17b1 raise the question of whether foxl2 might not regulate hsd17b1 . In fact, a recent study revealed that FOX proteins in the human genome, including FOXL2 , stimulate tumor suppressor TP53, acting as upstream regulators of this protein (Choi et al, 2022). Moreover, in porcine granulosa, TP53 positively regulates transcription and translation of Hsd17b1 (Yuan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…FOXA1 is a pioneer of epigenetic reprogramming in both stem cells and cancer cells and is involved in DNA repair complex formation and DNA demethylation [ 67 , 68 ]. Although both genes are known cancer drivers, the cooperative role of these two genes in cancer has largely not been fully elucidated until recently [ 69 ]. Nevertheless, the association between Hypo-MS4 and neoantigen load as well as the suppression of immune responses in the TIME further strengthened the relationship between FOXA1 activity and cancer immunity.…”
Section: Discussionmentioning
confidence: 99%